(3WQGFa GdWQa hXQGFa GdfWas - (3GdMSjf Hf eMeO Hf YHO GdhgGH, GdHGQY GdHZOGOj , CHh YHO Gddg,J (B524 (3g` s
(3ChdgG (B:s
(3hSejJg HWQGFa GdWQa hXQGFa GdfWa hHhHJg Ydi YOO GdHQhL GdEKfi YTQ GdHGH GdChd aj GdMce hGdCeKGd heG jMSf efgG aj GdcJGHI hGdebGd s
(3BNQgG (B:s
(3hef jnQ Pdc GdhLg GdefOi abO dbi GdSYGOI hGdfLGMG hbO UGQ Gdghi LOG HbdHj hcfJ CQGg ef bHd GdeOGMG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GfXQ GdLRA GdChd GdQbe (B589-590 (3COHs
(3HChdgG Jedc eDQN SfI (B957(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B255 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B54s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B19 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1109s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs